2023
DOI: 10.3389/fnmol.2023.1247422
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of brain-derived neurotrophic factor signaling in the pathogenesis of stress-related brain diseases

Tadahiro Numakawa,
Ryutaro Kajihara

Abstract: Neurotrophins including brain-derived neurotrophic factor, BDNF, have critical roles in neuronal differentiation, cell survival, and synaptic function in the peripheral and central nervous system. It is well known that a variety of intracellular signaling stimulated by TrkB, a high-affinity receptor for BDNF, is involved in the physiological and pathological neuronal aspects via affecting cell viability, synaptic function, neurogenesis, and cognitive function. As expected, an alteration of the BDNF/TrkB system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…Structurally, studies have shown that stress changes neuronal morphology and reduces neuronal proliferation and hippocampal volume [8]. Such dysregulation of the HPA axis has been suggested to be involved in the pathogenesis of not only mental disorders but also AD [9]. As expected, a variety of studies show that GCs affect neurons and induce neurobiological changes (molecular and cellular levels) via activation of their receptors, the glucocorticoid receptor (GR), or the mineralocorticoid receptor (MR).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Structurally, studies have shown that stress changes neuronal morphology and reduces neuronal proliferation and hippocampal volume [8]. Such dysregulation of the HPA axis has been suggested to be involved in the pathogenesis of not only mental disorders but also AD [9]. As expected, a variety of studies show that GCs affect neurons and induce neurobiological changes (molecular and cellular levels) via activation of their receptors, the glucocorticoid receptor (GR), or the mineralocorticoid receptor (MR).…”
Section: Introductionmentioning
confidence: 89%
“…However, after ND exposure, downregulated BDNF levels in the perinatal period and puberty (P40) were observed, suggesting that early-life DEX exposure caused interference in BDNF signaling during neuronal development [39]. A lot of evidence has shown the downregulation of the BDNF system after GC stress [9] (see Figure 1).…”
Section: Glucocorticoid Stress Bdnf and Neuronal Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mindfulness-induced increases in BDNF could potentially counteract or modulate these structural changes, offering protection against addiction-related neuroadaptations. Furthermore, chronic stress has been linked to alterations in BDNF-TrkB signaling [202], providing a potential link between mindfulness, stress reduction, and the modulation of neurotrophic factors in the context of methamphetamine dependency. By reducing stress, mindfulness may contribute to maintaining or enhancing BDNF expression, particularly in dopaminergic neurons, and counteract the negative impact of addictive drugs.…”
Section: Neurotrophic and Vascular Effect Of Mindfulness On Neuroplas...mentioning
confidence: 99%